Analysis of Workload Measurement Using Cardiovascular Load (CVL) and Bourdon Wiersma at PT. XYZ - Sunardi; Mochamad Tutuk Safirin; Isna Nugraha; Nico Aliffian Vollytanio Putra (Nusantara Science and Technology Proceedings)
Many companies still do not prioritize occupational health and safety, causing a large workload to be borne both physically and mentally. It affects the workers ' fatigue and will affect performance. Work fatigue is a symptom associated with decreased work efficiency, skills, boredom, and increased anxiety. PT. XYZ is a manufacturing company, which produce refractory stone from clay as the main raw material. The production process uses human-machine power, lack of rest time, overtime to achieve production targets, repetitive and standing work, and a long-distance between milling stations and raw material processing. A few people only carry out the final part of the process. With this problem, this study uses Cardiovascular Load and Bourdon Wiersma to slow down worker fatigue and is expected to help measure worker fatigue to provide a solution in slowing down worker fatigue. The number of samples used as many as 20 workers. The results obtained from the analysis of this work system are shift one and shift two have different levels of fatigue, namely shift one high category and shift two low categories, as well as the mental load shift one is low while shift two is high, therefore shift one needs to be the improvement in his physical load while shift two needs to improve his mental load. Corrective actions that can be taken in shift one are to increase the rest time from 45 minutes to 60 minutes, implement a worker rolling system, and improve workplace conditions to make it more ergonomic. Corrective actions that can be taken in shift two are providing music, arranging work shifts such as rolling shifts, and adding rest periods.